Analysis of Hardness on the Tapping Knife of Rubber Plants Made of Medium Carbon Steel Resulting from Quenching Process with Different Cooling Mediums - Hendri Nurdin; Remon Lapisa; Budi Syahri; Niko Adima Brawira (Universitas Negeri Padang, 2022)
The quenching process carried out by the Blacksmith was still simple and used regular water cooling. This results in the knife not having a good value of hardness. This study aimed to analyze the effects of quenching with different cooling media on the hardness of the JIS SUP 9 knife from Blacksmith. The research method used an experimental method with research objects made of carbon steel per leaf or the JIS SUP 9 which was given hardening with a temperature of 800 ° C with a holding time of 30 minutes then quenching with water cooling media and oil. The data analysis found that the knife quenching with water had an average hardness of 295.6 HVN, Oil had an average hardness of 720.7 HVN, and control specimens with a hardness of 256.6 HVN. Thus, the medium quenching oil has the highest value of hardness, while the oil quenching media also has a good hardness value with no acceleration of the process of expansion. From the results of the study, the authors recommend in the quenching process use of oil cooling media, as well as adding variations of cooling media to get a better hardness value.